ANTECEDENTS OF ONLINE LEARNING EFFECTIVENESS AND ITS IMPACT ON EDUCATIONAL ETHICS: A COMPARATIVE STUDY BETWEEN INDIA AND MALAYSIA - Tamana Anand; Sarvjeet Kaur Chatrath; Jayalakshmy Ramachandran; Gurdip Batra; Naomi F. Dale; Hong Kay Tze; Rama Bansal; Dhanya Govindakrishnan (Journal of Applied Structural Equation Modelling, 2024)
COVID-19 pandemic has forced the implementation of a new normal for all businesses leading to an increase in stress levels for many including educators and students. Ethics in education was questioned by professional bodies due to online exams. The objective of this study is to determine the antecedents of student online learning effectiveness and its impact on educational ethics. The study compares Malaysia and India since some Indian educational institutions had been implementing online teaching prior to the pandemic. Data was collected through a survey method. 571 questionnaires from students across Malaysia and India were analyzed using SPSS and PLS-SEM. It was found that physical, psychological, intellectual, and emotional attributes were significant in predicting learning effectiveness which in turn had an impact on educational ethics. Intellectual attributes were the most important predictor of learning effectiveness. The emotional and psychological attributes had a small impact on learning effectiveness. Furthermore, physical attributes had trivial effects on the learning effectiveness. A T-test comparing mean differences between the two countries revealed that there were no significant differences in learning effectiveness between students of both countries while educational ethics was more evident among Indian students as compared to Malaysian students. The key implication is the need for educational institutions and educators to develop pedagogies to stimulate students’ intellectual abilities during online teaching to preserve educational ethics. HEIs must support the students psychologically, emotionally and encourage themselves to keep physically active during the phase of online classes. Institutions must take ample steps to ensure that educational ethics is not affected as a result of the new normal failing which could prove detrimental in the long run for students and institutions. This will help to curb unethical practices during online examinations and mitigate academic dishonesty. Our findings regarding various attributes of online learning effectiveness add profoundly to literature and help to understand antecedents contributing to successful learning effectiveness which leads to positive educational ethics in both the countries.